Admission glycemia associated with mortality and hospital stay in a multidisciplinary service of a Peruvian national hospital - García-Ruiz , Víctor Raúl (2023)
Objective: Evaluate the association between glycemia on admission and adverse outcomes in hospitalized patients with COVID19 in a Peruvian national hospital.  Methods: Retrospective, observational cohort study. We collected data from electronic medical records of COVID19 patients in a medical specialties service. Patients were classified according to blood glucose levels on admission: ≤ and >140mg/dL. Primary outcome was mortality, and the secondary a composite that included mortality, septic shock, mechanical ventilation, or transfer to ICU. We also evaluated hospital stay and a multivariate logistic regression sub analysis was performed in diabetic patients. Results: 169 patients were evaluated. The mean age was 61 years, 64.5% were male. 71% had at least one comorbidity, the most frequent: arterial hypertension (34%), obesity (30%) and diabetes (26%). 70% presented tomographic gravity. Median blood glucose at admission was 126.5mg/dL (IQR: 109-157mg/dL), one of every 3 had blood glucose levels >140mg/dL. Mortality rate was 9700 deaths per 100000 person-weeks, with a frequency of 21.3%. No significant difference was found between hyperglycemia and normoglycemia, mortality and in composite outcome. Patients with hyperglycemia on admission had longer hospital stay than normoglycemic patients (19 vs 13 days, p<0.01). In sub-analysis with multivariate logistic regression for composite outcome among diabetic patients, admission blood glucose >180mg/dL presented OR of 6.42 (95% CI: 1.07-38.6) for composite outcome, adjusted for age and clinical severity at admission. Conclusions: Hyperglycemia at admission was associated with a longer hospital stay and diabetic patients with hyperglycemia >180mg/dL had a 6-fold increased risk of presenting an adverse outcome.